2017
DOI: 10.1155/2017/2873030
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Oxidative Stress and Inflammation in Ascites and Plasma in Patients with Platinum‐Sensitive, Platinum‐Resistant, and Platinum‐Refractory Epithelial Ovarian Cancer

Abstract: Diverse proinflammatory biomarkers and oxidative stress are strongly associated with advanced epithelial ovarian cancer (EOC). Objective. To determine the behavior of markers of oxidative stress and inflammation in plasma and ascites fluid in patients with platinum-sensitive, platinum-resistant, and platinum-refractory EOC. Methods. A prospective cohort study. The colorimetric method was used to determine levels of the markers 8-isoprostanes (8-IP), lipid peroxidation products (LPO), and total antioxidant capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
16
1
1
Order By: Relevance
“…While the lack of sensitivity of the AmplexRed assay prevented us to accurately measure H 2 O 2 levels in ascites fluid, we observed that static oxidation reduction potential (ORP) was greatly variable among HGSA ascites specimens, ranging from 90.5 to 165.4 mV, and not specifically elevated compared to normal plasma sORP values that have been previously reported to range from 120 to 180 mV [38], [39], [40]. Canton-Romero et al recently demonstrated that ovarian cancer ascites display increased levels of 8-isoprostane and lipid peroxidation products compared to normal plasma [16]. Interestingly, it was also reported that ascites concomitantly increase their total antioxidant capacity [16].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…While the lack of sensitivity of the AmplexRed assay prevented us to accurately measure H 2 O 2 levels in ascites fluid, we observed that static oxidation reduction potential (ORP) was greatly variable among HGSA ascites specimens, ranging from 90.5 to 165.4 mV, and not specifically elevated compared to normal plasma sORP values that have been previously reported to range from 120 to 180 mV [38], [39], [40]. Canton-Romero et al recently demonstrated that ovarian cancer ascites display increased levels of 8-isoprostane and lipid peroxidation products compared to normal plasma [16]. Interestingly, it was also reported that ascites concomitantly increase their total antioxidant capacity [16].…”
Section: Discussionmentioning
confidence: 67%
“…Due to the presence of stromal and immune cells and high expression of pro-inflammatory cytokines, it has been proposed that the ascites environment is also marked by oxidative stress. A recent study demonstrated that 8-isoprostane levels are significantly elevated in ascites compared to normal serum [16]. However, it was also noted that total antioxidant capacity was concomitantly elevated in patient ascites [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for the need of GPx3 in tumor-derived ascites is the observed increase in lipid peroxides in this fluid. For example, in ovarian cancer ascites, soluble lipid peroxides were increased in patients that were refractory to platinum-based chemotherapy [137]. The identification and role of specific substrates of GPx3 in tumors, in particular soluble lipid hydroperoxides in the tumor microenvironment and basement membranes, require further attention.…”
Section: Discussionmentioning
confidence: 99%
“…В случае платинорезистентного и платинорефрактерного течения РЯ наблюдается дисрегуляция между окислителями, антиоксидантами и провоспалительными цитокинами Levels of IL-6, 8-IP in ascites compared with plasma levels are higher, and TNF-α levels are lower. In the case of platinum-resistant and platinum-refractory OC flow, there is disregulation between oxidants, antioxidants and pro-inflammatory cytokines [28] Комбинация высокого уровня TNF-α и IL-6 до лечения коррелирует с диссеминацией процесса и худшей выживаемостью без прогрессирования…”
Section: белковый компонент асцитаunclassified